2018
DOI: 10.1111/jopr.12750
|View full text |Cite
|
Sign up to set email alerts
|

Management of Challenging Esthetic Anterior Cases with Limited Restorative Space: A Clinical Report

Abstract: With careful restorative planning and surgical placement, dental implants can be used to support and retain a wide range of esthetic prostheses. When implant planning or surgical executions are less than ideal, however, the resulting restorative space can be a significant obstacle to successful treatment. The aim of this article is to describe the use of a customized anterior bar to support a partial overdenture prosthesis for a youthful patient with a high smile line and a limited restorative space of 6 mm. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Moreover, they found that only 4% of the subjects exposed their upper first molars when smilingthis finding being clearly different from the 20% recorded in our series. Aesthetic restoration of the visible posterior teeth may prove necessary in order to secure a harmonious outcome [49]. This is an important factor when planning anterior restorations, since consideration is required of both smile width and the number of teeth exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that only 4% of the subjects exposed their upper first molars when smilingthis finding being clearly different from the 20% recorded in our series. Aesthetic restoration of the visible posterior teeth may prove necessary in order to secure a harmonious outcome [49]. This is an important factor when planning anterior restorations, since consideration is required of both smile width and the number of teeth exposed.…”
Section: Discussionmentioning
confidence: 99%